Lithium metal interface modification method and lithium metal battery

By adsorbing and applying pressure on the carrier material, the modification liquid is closely bonded to the lithium metal surface to form a uniform artificial solid-liquid interface, which solves the problem of wetting in the interface modification of lithium metal battery and improves the cycle life and cost-effectiveness of the battery.

CN119252872APending Publication Date: 2025-01-03ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411335746.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing lithium metal battery modification methods are greatly affected by wetting, resulting in uneven thickness of the ASEI film at the lithium metal interface, inconsistent component distribution, and limited cycle life.

Method used

The carrier material is used to adsorb the modification liquid, and the carrier material is closely bonded to the lithium metal surface by applying preset pressure. After removing the carrier material, it is dried to form a uniform artificial solid-liquid interface. A porous polymer film is used as the carrier material. Control porosity and thickness, and optimize the composition and dosage of the modification liquid.

Benefits of technology

It improves the thickness and component distribution consistency of the ASEI film on the lithium metal surface, inhibits the growth of lithium dendrites, extends the cycle life of lithium metal batteries, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252872A_ABST
    Figure CN119252872A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium metal interface modification method and a lithium metal battery, and the modification method comprises the following steps: carrying out surface treatment on lithium metal to obtain treated lithium metal; adsorbing the modification liquid by adopting a carrier material; placing the carrier material adsorbing the modification liquid on the treated lithium metal surface; applying a preset pressure to the carrier material; and removing the carrier material, standing and drying to obtain the lithium metal containing the artificial solid-liquid interface. The modification liquid is adsorbed to the surface of the lithium metal by adopting the carrier material, and the carrier material and the lithium metal are tightly attached through pressure, so that the modification liquid and the lithium metal can be fully subjected to in-situ chemical reaction, and the ASEI film on the modified lithium metal surface is uniform in thickness and relatively high in flatness; according to the lithium metal surface modification method, the thickness consistency and component distribution consistency of the lithium metal artificial solid-liquid interface can be improved, the modified lithium metal interface can effectively inhibit growth of lithium dendrites, and the cycle life of a lithium metal battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a method for modifying a lithium metal interface and a lithium metal battery. Background Art

[0002] With the rapid development of science and technology and the widespread popularity of electronic devices, electric vehicles and other fields, people have an increasing demand for high-efficiency, high-energy-density batteries. Traditional battery technology can no longer meet this growing demand, so new battery technologies need to be developed to meet the urgent needs of the market. Among these new batteries, lithium metal batteries have attracted much attention because lithium metal battery systems have higher energy density. However, lithium metal batteries face many challenges in practical applications, such as impractical rate performance, unsafe cycle conditions and limited cycle life. In order to solve these problems, researchers often start from lithium metal materials and treat and modify the surface of lithium metal.

[0003] Among the modification methods of in-situ reactions, drip coating, immersion and spraying are all commonly used modification techniques. Among them, drip coating technology can accurately control the amount of modification liquid used, but its modification consistency is affected by wettability. The ASEI (Artificial Solid Electrolyte Interphase) film is often thick and concentrated at the location where the droplet initially drips, while the ASEI film is thin and the product is scarce in the edge area of ​​lithium metal; immersion can effectively solve the wetting problem, and the thickness and composition of the formed ASEI film are evenly distributed and consistent, but the modification liquid is often excessive, and the production loss is large; although the spraying technology has a controllable amount of modification liquid, low production loss and good product consistency, it is also affected by wettability, and the spraying equipment is expensive and the cost is high. Summary of the invention

[0004] The main purpose of the present invention is to provide a lithium metal interface modification method and a lithium metal battery, aiming to solve the problem that the existing lithium metal modification method is greatly affected by wettability.

[0005] To achieve the above object, the present invention provides a method for modifying a lithium metal interface, the modification method comprising:

[0006] Adopting a carrier material to adsorb the modification liquid;

[0007] placing a carrier material for adsorbing the modification solution on the surface of the lithium metal;

[0008] applying a preset pressure to the carrier material;

[0009] The support material is removed and dried to obtain lithium metal containing an artificial solid-liquid interface.

[0010] Preferably, the support material is a porous polymer film.

[0011] Preferably, the material of the porous polymer film is selected from at least one of polyethylene, polypropylene, polyvinyl chloride, polyester film, cellulose, polysulfone, polyimide, and fluorine-containing polymer.

[0012] Preferably, the porosity of the porous polymer film is 20% to 60%;

[0013] And / or, the thickness of the porous polymer film is 10 μm to 30 μm.

[0014] Preferably, the preset pressure is 100KPa to 900KPa;

[0015] And / or, the pressure is applied for a period of 30 min to 120 min.

[0016] Preferably, the modification solution comprises a solute and a solvent;

[0017] The solute of the modification solution is selected from at least one of ammonium fluoride, zirconium oxynitrate, phosphoric acid, and dodecylbenzene sulfonic acid;

[0018] And / or, the solvent of the modification solution is at least one selected from dimethyl sulfoxide, ethylene carbonate, ethyl methyl carbonate, acetonitrile and methanol.

[0019] Preferably, the adsorption amount of the modification solution in the carrier is 20 μL to 50 μL.

[0020] Preferably, the lithium metal is selected from one of pure lithium metal strip, copper-based lithium strip, and polymer-based lithium strip;

[0021] And / or, the thickness of the lithium metal is 10 μm to 1000 μm.

[0022] Preferably, before the step of placing the carrier material for adsorbing the modification solution on the surface of the lithium metal, the method further comprises the following steps:

[0023] Surface treatment of lithium metal.

[0024] Preferably, the surface treatment includes one or both of rolling treatment and polishing treatment.

[0025] The present invention further proposes a lithium metal battery, comprising a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode; wherein the negative electrode is lithium metal containing an artificial solid-liquid interface prepared by the method described above.

[0026] The beneficial effect of the technical solution of the present invention is that: the present invention uses a carrier material to adsorb the modification liquid onto the surface of the lithium metal, and uses pressure to make the carrier material and the lithium metal closely fit, so that the modification liquid can fully react with the lithium metal in situ, so that the thickness of the ASEI film on the surface of the modified lithium metal is uniform and the flatness is high. The lithium metal surface modification method of the present invention can improve the thickness consistency and component distribution consistency of the lithium metal artificial solid-liquid interface, and the modified lithium metal interface can effectively inhibit the growth of lithium dendrites and improve the cycle life of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 4 is a flow chart of the steps of the lithium metal interface modification method according to an embodiment of the present invention.

[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0029] The scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, top, bottom, side...) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0031] It should also be noted that when an element is referred to as being "fixed on" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element at the same time. When an element is referred to as being "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0032] In addition, the descriptions involving "first", "second", etc. in the embodiments of the present invention are only for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features.

[0033] Among the existing new batteries, lithium metal batteries have attracted much attention because the lithium metal battery system has a higher energy density. The gram capacity of lithium metal is as high as 3860mAh / g (11 times higher than graphite), and the redox potential is as low as -3.04V compared with the standard hydrogen electrode (which means the discharge voltage platform is higher). According to our calculations, if the graphite negative electrode in the battery is replaced with lithium metal, the volume ED (energy density) gain of the battery will increase by up to 62%, and the weight ED gain can increase by up to 45%, which means that at the same volume and weight, the battery can store more energy, and electric vehicles, mobile phones and other devices will have a longer battery life. However, lithium metal batteries face many challenges in practical applications, such as impractical rate performance, unsafe cycle conditions and limited cycle life. In order to solve these problems, researchers often start from lithium metal materials and treat and modify the surface of lithium metal. However, existing modification methods are affected by wettability or are costly.

[0034] In view of the technical defects existing in the related art, the present invention proposes a method for modifying the lithium metal interface, see Figure 1 , the modification method comprises:

[0035] Step S100, using a carrier material to adsorb the modification liquid;

[0036] Step S200, placing a carrier material for adsorbing the modification solution on the treated lithium metal surface;

[0037] Step S300, applying a preset pressure to the carrier material;

[0038] Step S400, removing the carrier material, drying, and obtaining lithium metal containing an artificial solid-liquid interface.

[0039] In this embodiment, a carrier material is used to adsorb the modification liquid onto the surface of the lithium metal, and pressure is used to make the carrier material and the lithium metal closely fit together, so that the modification liquid can fully react with the lithium metal in situ, so that the thickness of the ASEI film on the surface of the modified lithium metal is uniform and the flatness is high. The lithium metal surface modification method of the present application can improve the thickness consistency and component distribution consistency of the artificial solid-liquid interface of the lithium metal, and the modified lithium metal interface can effectively inhibit the growth of lithium dendrites and improve the cycle life of the lithium metal battery.

[0040] In some embodiments, the support material is a porous polymer film.

[0041] In some embodiments, the material of the porous polymer film is selected from at least one of polyethylene, polypropylene, polyvinyl chloride, polyester film, cellulose, polysulfone, polyimide, and fluorine-containing polymer.

[0042] Specifically, the porous polymer film needs to have good adsorption properties for the modification liquid and not chemically react with the modification liquid. The porous polymer films of the above materials all have excellent chemical stability and can be used as good carrier materials.

[0043] In some embodiments, the porosity of the porous polymer film is 20% to 60%; and / or the thickness of the porous polymer film is 10 μm to 30 μm.

[0044] In this embodiment, the thickness and porosity of the porous polymer film will affect the modification effect. Under the condition of excessive modification liquid usage, the smaller the thickness and the lower the porosity, the less the film will adsorb the modification liquid. In other words, the less the degree of reaction between the modification liquid and lithium metal, the lower the thickness of the artificial solid-liquid interface formed, and even the ASEI film thickness distribution may be uneven, thereby affecting the embedding or escape path of lithium ions on the lithium metal surface during the cycle. Although an overly thick film and a large porosity can avoid this situation, the consumption of the modification liquid is too large, which is not conducive to reducing costs.

[0045] In some embodiments, the preset pressure is 100 KPa to 900 KPa; and / or the pressure is applied for 30 min to 120 min.

[0046] Specifically, the time for applying pressure is the modification time. If the time is too short, the reaction is not complete. If the time is too long, the reaction can be fully carried out, but the process is time-consuming. The pressure applied during the modification process needs to be controlled within a reasonable range. When the pressure exceeds the reasonable value, it will produce indentations on the surface of the lithium metal. These indentations will increase the specific surface area of ​​the lithium metal, increase the risk of by-product accumulation, and ultimately lead to a shorter cycle life. If the pressure is too low, it cannot ensure that the modification liquid fully infiltrates the surface of the lithium metal.

[0047] In some embodiments, the modification solution includes a solute and a solvent; the solute of the modification solution is selected from at least one of ammonium fluoride, zirconium oxynitrate, phosphoric acid, and dodecylbenzene sulfonic acid; and / or the solvent of the modification solution is selected from at least one of dimethyl sulfoxide, ethylene carbonate, ethyl methyl carbonate, acetonitrile, and methanol.

[0048] In this embodiment, the solute of the modification solution reacts in situ with the lithium metal to form an ASEI film on the surface of the lithium metal, while the solvent of the modification solution needs to be inert to the lithium metal and the ASEI film formed by the reaction; for volatile solvents, the porous polymer film should be bonded to the lithium metal within 2 minutes after absorbing the modification solution.

[0049] In some embodiments, the adsorption amount of the modification solution in the carrier is 20 μL to 50 μL.

[0050] The amount of modification solution adsorbed has a significant impact on the modification effect. When the amount of modification solution adsorbed is less than 20 μL, it may not be able to completely cover the lithium metal surface, thus forming an incomplete or uneven ASEI film. When the amount of modification solution used is more than 50 μL, it will also have a negative impact on the modification effect, which may cause the ASEI film to be too thick or even overflow the edge of the lithium metal interface, causing unnecessary waste and uneven film distribution. Furthermore, the amount of modification solution used directly affects the drying time of the modified layer. The right amount of modification solution helps to form a uniform film and dry it within the appropriate time. However, excessive use will prolong the drying time, while insufficient use may cause the film to be discontinuous and affect its stability.

[0051] In some embodiments, the lithium metal is selected from one of a pure lithium metal strip, a copper-based lithium strip, and a polymer-based lithium strip; and / or the thickness of the lithium metal is 10 μm to 1000 μm.

[0052] In this embodiment, since the lithium metal interface modification process in this application is achieved by an in-situ chemical reaction between the modification solution solute and the lithium metal, that is, during the modification process, the lithium metal will also be consumed, so the lithium metal needs to have a certain thickness; further, the thickness of the lithium metal will have a significant impact on the cycle performance, because the lithium metal will be continuously consumed due to its own high activity during repeated embedding and extraction, or react with the electrolyte to generate by-products, or form "dead lithium", therefore, in order to manufacture a lithium metal battery with long cycle stability, the lithium metal needs to have a reasonable initial thickness. When the thickness of the lithium metal is less than 10μm, the cycle is too short, and this type of lithium metal battery has no use value; when the thickness of the lithium metal is higher than 1000μm, the lithium metal surplus is too large, although it can effectively extend the cycle life, but it will cause the overall energy density of the battery to drop seriously, and this type of battery also has no practical value.

[0053] In some embodiments, before the step of placing the carrier material for adsorbing the modification solution on the surface of the lithium metal, the step further includes:

[0054] Surface treatment of lithium metal.

[0055] Preferably, the surface treatment includes one or both of a rolling treatment and a polishing treatment.

[0056] In this embodiment, there is a layer of oxide on the surface of lithium metal. The dense structure of the oxide will affect the in-situ chemical reaction between the solute of the modification solution and lithium metal. Removing the oxide through surface treatment is beneficial to improving the modification uniformity of the lithium metal interface.

[0057] The present invention further proposes a lithium metal battery, which includes a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode; wherein the negative electrode is lithium metal containing an artificial solid-liquid interface prepared by the method as described above.

[0058] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0059] Example 1

[0060] A method for modifying a lithium metal interface, comprising:

[0061] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0062] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0063] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0064] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0065] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0066] Example 2

[0067] A method for modifying a lithium metal interface, comprising:

[0068] Step S100, polishing the lithium metal with a thickness of 30 μm to obtain processed lithium metal;

[0069] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0070] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0071] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0072] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0073] Example 3

[0074] A method for modifying a lithium metal interface, comprising:

[0075] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0076] Step S200, using a porous polyethylene film with a thickness of 30 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0077] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0078] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0079] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0080] Example 4

[0081] A method for modifying a lithium metal interface, comprising:

[0082] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0083] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 60% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0084] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0085] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0086] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0087] Example 5

[0088] A method for modifying a lithium metal interface, comprising:

[0089] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0090] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 20 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0091] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0092] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0093] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0094] Example 6

[0095] A method for modifying a lithium metal interface, comprising:

[0096] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0097] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0098] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0099] Step S400, applying a pressure of 50 KPa to the porous polyethylene film for 30 minutes;

[0100] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0101] Example 7

[0102] A method for modifying a lithium metal interface, comprising:

[0103] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0104] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0105] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0106] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 60 minutes;

[0107] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0108] Example 8

[0109] A method for modifying a lithium metal interface, comprising:

[0110] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0111] Step S200, using a porous polypropylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0112] Step S300, placing a porous polypropylene film adsorbing the modification liquid on the treated lithium metal surface;

[0113] Step S400, applying a pressure of 100 KPa to the porous polypropylene film for 30 minutes;

[0114] Step S500, removing the porous polypropylene film, standing and drying, and obtaining lithium metal containing an artificial solid-liquid interface.

[0115] Example 9

[0116] A method for modifying a lithium metal interface, comprising:

[0117] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0118] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is ammonium fluoride, and the solvent of the modification solution is methanol;

[0119] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0120] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0121] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining lithium metal containing an artificial solid-liquid interface.

[0122] Comparative Example 1

[0123] A method for modifying a lithium metal interface, comprising:

[0124] Step S100, polishing the lithium metal with a thickness of 8 μm to obtain processed lithium metal;

[0125] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0126] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0127] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0128] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0129] Comparative Example 2

[0130] A method for modifying a lithium metal interface, comprising:

[0131] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0132] Step S200, using a porous polyethylene film with a thickness of 5 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0133] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0134] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0135] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0136] Comparative Example 3

[0137] A method for modifying a lithium metal interface, comprising:

[0138] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0139] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 10% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0140] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0141] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0142] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0143] Comparative Example 4

[0144] A method for modifying a lithium metal interface, comprising:

[0145] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0146] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 10 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0147] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0148] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0149] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0150] Comparative Example 5

[0151] A method for modifying a lithium metal interface, comprising:

[0152] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0153] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0154] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0155] Step S400, applying a pressure of 1000 KPa to the porous polyethylene film for 30 minutes;

[0156] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0157] Comparative Example 6

[0158] A method for modifying a lithium metal interface, comprising:

[0159] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0160] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0161] Step S300, placing a porous polyethylene film adsorbing the modification liquid on the treated lithium metal surface;

[0162] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 10 minutes;

[0163] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0164] Comparative Example 7

[0165] A method for modifying a lithium metal interface, comprising:

[0166] Step S100, polishing the lithium metal with a thickness of 100 μm to obtain the processed lithium metal;

[0167] Step S200, using a porous polyethylene film with a thickness of 20 μm and a porosity of 40% to absorb 50 μL of a modification solution, and leaving it to stand until the solvent is completely volatilized; wherein the solute of the modification solution is zirconium oxynitrate, and the solvent of the modification solution is dimethyl sulfoxide;

[0168] Step S300, placing a porous polyethylene film for absorbing the solute of the modification solution on the surface of the treated lithium metal;

[0169] Step S400, applying a pressure of 100 KPa to the porous polyethylene film for 30 minutes;

[0170] Step S500, removing the porous polyethylene film, standing it to dry, and obtaining modified lithium metal.

[0171] Performance Testing

[0172] 1. Flatness test: The modified lithium metal is cut longitudinally to test the flatness of the ASEI film on the surface of the modified lithium metal. The flatness of the ASEI film in one plane is the difference between the maximum thickness and the minimum thickness of ASEI.

[0173] 2. Cycle life test: The modified lithium metal in Examples 1 to 7 and Comparative Examples 1 to 7 was cut into small discs with a diameter of 16 mm, and two of the small discs were used to assemble a 2032 symmetrical battery, wherein the electrolyte was an EC / EMC electrolyte with a concentration of 1M LiPF6, EC:EMC=3:7, and the diaphragm was a 14μm thick PE diaphragm. Five symmetrical batteries were taken for each battery, and the current density was set to 1mAh / cm 2 , set the single charge surface capacity to 1mAh / cm 2 , charge and discharge cycles were carried out at room temperature until the polarization voltage was greater than 0.2V, and the cycle life of the batteries in the embodiments and comparative examples was compared.

[0174] The specific test steps are as follows:

[0175] (1) Leave for 5 minutes at 1 mAh / cm 2 The current is constant current charged for 1h;

[0176] (2) Leave for 5 min, at 1 mAh / cm 2 The current is discharged at a constant current for 1h;

[0177] (3) Repeat steps (1)-(2) until the polarization voltage is greater than 0.2 V;

[0178] (4)End.

[0179] 3. Impedance test: The modified lithium metal in Examples 1 to 7 and Comparative Examples 1 to 7 was cut into small discs with a diameter of 16 mm, and two of the small discs were used to assemble a 2032 symmetrical battery, wherein the electrolyte was an EC / EMC electrolyte with a concentration of 1M LiPF6, EC:EMC=3:7, and the diaphragm was a 14 μm thick PE diaphragm. The symmetrical battery was subjected to EIS test, and the electrochemical test instrument was Shanghai Chenhua electrochemical workstation, and the frequency range was set to 10 -2 Hz~10 5 Hz.

[0180] The test results of Examples 1 to 7 and Comparative Examples 1 to 7 are shown in Table 1.

[0181] Table 1 Performance test results

[0182] sample ASEI Flatness Cycle life impedance Example 1 46nm 580h 17.02Ω Example 2 45nm 345h 16.87Ω Example 3 40nm 456h 14.32Ω Example 4 39nm 432h 13.24Ω Example 5 49nm 394h 19.02Ω Example 6 42nm 562h 14.98Ω Example 7 45nm 623h 15.97Ω Example 8 47mm 563h 17.67Ω Example 9 52mm 523h 21.02Ω Comparative Example 1 45nm 0h 18.02Ω Comparative Example 2 67nm 264h 22.34Ω Comparative Example 3 84nm 243h 29.08Ω Comparative Example 4 92nm 252h 34.05Ω Comparative Example 5 73nm 186h 27.82Ω Comparative Example 6 65nm 234h 22.31Ω Comparative Example 7 195nm 249h 50.43Ω

[0183] It can be seen from Examples 1 and 2 and Comparative Example 1 that a reduction in the thickness of lithium metal leads to a decrease in cycle life. This is because during the cycle, lithium metal, due to its own high activity, reacts with the electrolyte to generate by-products, resulting in loss of lithium metal. When the lithium metal is consumed, the battery will fail.

[0184] It can be seen from Examples 1, 3 to 7 and Comparative Examples 2 to 6 that the film thickness, porosity, adsorption amount, and pressure application time are related to the effective modification amount. Under the condition of uniform distribution, the effective modification amount represents the thickness of the artificial solid-liquid interface. The thickness will affect the ionic conductivity of ions at the artificial solid-liquid interface and thus affect the cycle life of the battery. The pressure applied during the modification process has little effect on the cycle life within a reasonable range, but when the pressure exceeds a reasonable value, indentations will be generated on the surface of the lithium metal. These indentations will increase the specific surface area of ​​the lithium metal, increase the risk of by-product accumulation, and ultimately lead to a shorter cycle life.

[0185] Comparative Example 7 is an in-situ generation of an artificial solid-liquid interface through a pressure-triggered solid-solid reaction. According to the test results of Example 1 and Comparative Example 7, it can be seen that the reaction conditions between solids are very harsh and the compatibility with the chemical system is poor. Drying the film after adsorbing the modifying liquid will affect the formation of the artificial solid-liquid interface. This is because the method of the present application lacks a catalyst to trigger a solid-solid reaction. The present application adopts a solid-liquid reaction method. The liquid substance in the solid-liquid reaction provides a better reaction environment, the contact between the reactants is sufficient, the efficiency is high, and the product distribution is uniform; secondly, the solid-liquid reaction can achieve precise control of the product composition and structure by changing the liquid composition and concentration; in addition, liquid substances are more convenient for transportation, mixing and separation in industrial production, thereby improving production efficiency and reducing costs.

[0186] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 7 that under specific electrolyte conditions, the impedance of the SEI layer is strongly correlated with the interface flatness. This is because the flatness of the lithium metal surface affects the uniformity of the SEI film, and the lithium ion insertion and extraction paths in thicker areas are longer, resulting in increased impedance.

[0187] The above descriptions are only partial or preferred embodiments of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.

Claims

1. A method for modifying a lithium metal interface, characterized in that: include: Adopting a carrier material to adsorb the modification liquid; placing a carrier material for adsorbing the modification solution on the surface of the lithium metal; applying a preset pressure to the carrier material; The support material is removed and dried to obtain lithium metal containing an artificial solid-liquid interface.

2. The method for modifying the lithium metal interface according to claim 1, characterized in that: The carrier material is a porous polymer film.

3. The method for modifying the lithium metal interface according to claim 2, characterized in that: The material of the porous polymer film is selected from at least one of polyethylene, polypropylene, polyvinyl chloride, polyester film, cellulose, polysulfone, polyimide, and fluorine-containing polymer.

4. The method for modifying the lithium metal interface according to claim 2 or 3, characterized in that: The porosity of the porous polymer film is 20% to 60%; And / or, the thickness of the porous polymer film is 10 μm to 30 μm.

5. The method for modifying the lithium metal interface according to claim 1, characterized in that: The preset pressure is 100KPa~900KPa; And / or, the pressure is applied for a period of 30 min to 120 min.

6. The method for modifying the lithium metal interface according to claim 1, characterized in that: The modification solution includes a solute and a solvent; The solute of the modification solution is selected from at least one of ammonium fluoride, zirconium oxynitrate, phosphoric acid, and dodecylbenzene sulfonic acid; And / or, the solvent of the modification solution is at least one selected from dimethyl sulfoxide, ethylene carbonate, ethyl methyl carbonate, acetonitrile and methanol.

7. The method for modifying the lithium metal interface according to claim 1, characterized in that: The adsorption amount of the modification solution in the carrier is 20 μL to 50 μL.

8. The method for modifying the lithium metal interface according to claim 1, characterized in that: The lithium metal is selected from one of pure lithium metal strip, copper-based lithium strip, and polymer-based lithium strip; And / or, the thickness of the lithium metal is 10 μm to 1000 μm.

9. The method for modifying the lithium metal interface according to claim 1, characterized in that: Before the step of placing the carrier material for adsorbing the modification solution on the surface of the lithium metal, the step further includes: Surface treatment of lithium metal.

10. The method for modifying the lithium metal interface according to claim 9, characterized in that: The surface treatment includes one or both of rolling treatment and polishing treatment.

11. A lithium metal battery, characterized in that: The lithium metal battery comprises a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode; wherein the negative electrode is lithium metal containing an artificial solid-liquid interface prepared by the method according to any one of claims 1 to 10.

Citation Information

Cited By

  • Artificial SEI membrane and preparation method thereof, negative pole piece and sodium ion battery

    CN120998944A

  • Artificial SEI film, preparation method thereof, negative electrode sheet and sodium-ion battery

    CN120998944B